Kasus Reaksi Transfusi pada Pasien Penerima Donor Darah di RSUD Sayang Kabupaten Cianjur Periode 2020-2022 - Purlinda, Devi Etivia; Nurhamida, Tsani Nisa (Poltekkes Kemenkes Semarang, 2024)
Blood transfusions must be performed based on appropriate indications, selecting the correct volume and type of component, and administered at the right time. The risk of transfusion reactions is inherent in nearly every transfusion process and can manifest clinical symptoms in patients. Hospitals must conduct oversight of the blood transfusion process, known as hemovigilance, to prevent transfusion reactions and enhance the safety of blood services. This study aims to determine the number of transfusion reaction cases in blood donor recipients at RSUD Sayang, Cianjur Regency, during the period from 2020 to 2022. This qualitative research utilizes a total sampling technique. The population comprises all blood donor recipients at RSUD Sayang, Cianjur Regency, from 2020 to 2022. The sample includes medical records data of transfusion reaction cases in blood donor recipients at RSUD Sayang, Cianjur Regency, from 2020 to 2022. The results indicate 35 cases of transfusion reactions. The majority of transfusion reaction cases in blood donor recipients were acute category I (mild) reactions, totaling 21 cases (60%). Patients with a history of previous transfusions predominantly experienced category I (mild) and category II (moderate) reactions, each with 12 cases (57.1%). Most acute reaction cases were category I (mild), with 20 cases (57.1%), occurring during transfusions with Packed Red Cells (PRC). The majority of acute transfusion reactions occurred after the administration of the first blood bag, with 17 cases (48.6%), and these reactions were primarily category I (mild).